Analisis Kurikulum Aqidah Akhlak Menggunakan Landasan Filosofis-Teologis, Psikologis, dan Sosiokultural di Madrasah Ibtidaiyah: Analysis of the Aqidah Akhlak Curriculum Using Philosophical-Theological, Psychological, and Sociocultural Foundations in Madrasah Ibtidaiyah - Karlaely, Irma (Perkumpulan Peneliti dan Pegiat Literasi, 2023)
This study analyzes the Aqidah Akhlak curriculum in Madrasah Ibtidaiyah using philosophical, theological, psychological, and sociocultural foundations. The research aims to evaluate the effectiveness of a thematic approach in teaching moral and faith values. This study employs content analysis methodology and interviews with teachers as the research design. The findings indicate that the thematic approach aids students in understanding and recalling moral principles, but there are shortcomings in practical application and comprehensive evaluation. Key findings suggest that improvements in teacher training and the use of information technology can enhance the effectiveness of this curriculum. The implications of this study contribute to Islamic education literature by highlighting the importance of a more integrated and adaptive approach in teaching religious values at the elementary school level.